THE IMPACT OF PHYSICAL FATIGUE ON WORK PRODUCTIVITY IN INTERVENING WORKLOAD IN THE REGIONAL DISASTER MANAGEMENT AGENCY (BPBD) OF NORTH SUMATERA - Winda Ardiani; Annisha Suvero Suyar; Dira Shafa (Sean Institute, 2023)
This research was conducted at the Regional Disaster Management Agency (BPBD) of North Sumatra Province, with the aim of analyzing the impact of physical fatigue on work productivity which is intervened by workload.The population is 110 employees who work at the Regional Disaster Management Agency (BPBD) of North Sumatra Province. The sampling method uses a random sample, where the sampling is done with a census sample so that the total is 110 respondents. physical fatigue and workload have a significant effect on work productivity in BPBD North Sumatra Province. Workload mediates the effect of physical fatigue on employee work productivity at BPBD North Sumatra Province. The correlation between physical fatigue and workload and also the correlation between physical fatigue and workload on work productivity can be categorized as moderate in BPBD North Sumatra Province